Overexpression of the 3’ half of the PHYB partially suppresses dwarfism in the brassinosteroid-insensitive bri1-5 mutant - Jeong, Yu Jeong; Park, Slki; Suh, Su Jeoung; Kwon, Soon Il; Cha, Richard; Kim, Yoong Eun; Choe, Sunghwa (Journal of plant biology = Singmul Hakhoe chi, 2016)
Brassinosteroids (BRs) control virtually every aspect of plant growth and development. BRs act alone or in combination with other signals. To identify the signaling components that interact with BRs, we screened for mutants that suppress the dwarf phenotypes of brassinosteroid insensitive 1-5 ( bri1-5 ) using an overexpression mutagenesis method. We established a mutant population by introducing a cDNA library in which cDNA was overexpressed under a constitutive promoter into Arabidopsis bri1-5 plants, which lacked a functional brassinosteroid (BR) receptor. One of the mutants, dubbed ‘ bri1-5 with long petioles’ ( blp ), was selected based on its suppression phenotype. blp contained a chimeric DNA consisting of the 3’ half of PHYB , a 2-bp insertion, and a part of the chloroplast ribosomal RNA gene. Re-introduction of the chimeric DNA into bri1-5 recapitulated the blp phenotype. Prompted by the phenotypic similarity between blp and phyB , we examined both the transcript and protein levels of PHYB in the mutants. The levels were lower in blp 35Spro:PHYB than in 35Spro:PHYB plants, suggesting that introduction of the chimeric gene interfered with the stability of PHYB transcripts. Genome-wide screening for a specific target phenotype resulted in the finding that overexpression of the 3’ half of PHYB in the sense direction can cause a loss-of-function phenotype, and that PHYB plays an important role in BR signaling. Our results validate overexpression mutagenesis as a method to identify the function of Arabidopsis genes.